2019
DOI: 10.1017/jog.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the total sub-debris ablation from point-scale ablation data on a debris-covered glacier

Abstract: Glaciological ablation is computed from point-scale data at a few ablation stakes that are usually regressed as a function of elevation and averaged over the area-elevation distribution of a glacier. This method is contingent on a tight control of elevation on local ablation. However, in debris-covered glaciers, systematic and random spatial variations of debris thickness modify the ablation rates. We propose and test a method to compute sub-debris ablation where stake data are interpolated as a function of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…d −1 for clean ice). A quadratic polynomial function was fitted on all the point ablation data from different years to understand the altitude dependency of ablation on the glacier following standard glaciological practice (Kaser and others, 2003; Shah and others, 2019). The polynomial function analysis provides a better description of the mass-balance variation and altitude/debris cover dependency (Figs S4–S8).…”
Section: Resultsmentioning
confidence: 99%
“…d −1 for clean ice). A quadratic polynomial function was fitted on all the point ablation data from different years to understand the altitude dependency of ablation on the glacier following standard glaciological practice (Kaser and others, 2003; Shah and others, 2019). The polynomial function analysis provides a better description of the mass-balance variation and altitude/debris cover dependency (Figs S4–S8).…”
Section: Resultsmentioning
confidence: 99%
“…It also varies with time due to stochastic and systematic changes in headwall-erosion rates (Banerjee and Wani, 2018). Additional sources of debris due to rockfall, debris avalanche and degradation of lateral moraines (Nakawo and others, 1986) add further noise to the debris-thickness distribution (Shah and others, 2019). Complex mass-balance processes like avalanche activity (Laha and others, 2017), and stochastic increase in local ablation due to thermokarst features like supraglacial ponds and ice-cliffs (Sakai and others, 2000), may modify the mass-balance profile.…”
Section: Resultsmentioning
confidence: 99%
“…4), and it is not clear which variable is more important in controlling the duration of sub-debris melt. Previous work on Satopanth Glacier in the Central Himalaya has demonstrated that debris thickness is more important than glacier elevation in controlling the magnitude of sub-debris melt (Shah and others, 2019). The shorter ablation season at higher elevation sites could be due to more effective heating over thinner debris layers (Steiner and Pellicciotti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that, in the absence of snowfall and phase changes within the debris, quasi-linear temperature profiles can be expected over the core ablation season in the Himalaya (Nicholson and Benn, 2013), which potentially simplifies the calculation of annual ablation from debris-covered glaciers. Furthermore, sub-debris melt appears to be more strongly controlled by debris thickness rather than glacier elevation (Shah and others, 2019). A step forward in understanding debris-covered glacier mass balance lies in observing how the conductive heat flux varies across the entire vertical debris profile, from the surface to the debris–ice interface.…”
Section: Introductionmentioning
confidence: 99%